PENGARUH TINGKAT PENDIDIKAN MASYARAKAT TERHADAP PARTISIPASI POLITIK DALAM PEMILIHAN BUPATI TAHUN 2014 DI KELURAHAN LEORAN KABUPATEN ENREKANG - Irmasugiati Irmasugiati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2017)
The political participation of the Leoran Village community in the 2014 regent election was relatively high, at 73.69%. This data was obtained from the number of people who participated as many as 1095 people divided by the number of permanent voters, namely 1486 people multiplied by 100%. Seeing the high political participation of the community, the authors are interested in examining how the influence of education level on people's political participation. The objectives of the study were: 1) to examine and analyze the influence of the level of public education on political participation in the 2014 regent election in Leoran Village, Enrekang Regency and 2) to determine the factors that influence the level of public political participation in the 2014 regent election in Leoran Village, District Enrekang. Samples were taken from voters who participated in the 2014 regent election in Leoran Village, Enrekang Regency as many as 92 people out of 1095 population. The data collection techniques used are: 1) observation, 2) interviews, 3) questionnaires, and 4) library research. The results of this study reveal that: The level of public education has a high influence (80.43%) on political participation in the 2014 regent election in Leoran Village, Enrekang Regency. The factors that influence the level of public political participation in the 2014 regent election in Leoran Village, Enrekang Regency are: political education (58.70%), political awareness (80.43%), political culture (67.39%), and socialization politics (65.22%).